Tailored topotactic chemistry unlocks heterostructures of magnetic intercalation compounds - Samra Husremović; Oscar Gonzalez; Berit H. Goodge; Lilia S. Xie; Zhizhi Kong; Wanlin Zhang; Sae Hee Ryu; Stephanie M. Ribet; Shannon S. Fender; Karen C. Bustillo; Chengyu Song; Jim Ciston; et al. (Nature Communications)
Abstract The construction of thin film heterostructures has been a widely successful archetype for fabricating materials with emergent physical properties. This strategy is of particular importance for the design of multilayer magnetic architectures in which direct interfacial spin-spin interactions between magnetic phases in dissimilar layers lead to emergent and controllable magnetic behavior. However, crystallographic incommensurability and atomic-scale interfacial disorder can severely limit the types of materials amenable to this strategy, as well as the performance of these systems. Here, we demonstrate a method for synthesizing heterostructures comprising magnetic intercalation compounds of transition metal dichalcogenides (TMDs), through directed topotactic reaction of the TMD with a metal oxide. The mechanism of the intercalation reaction enables thermally initiated intercalation of the TMD from lithographically patterned oxide films, giving access to a family of multi-component magnetic architectures through the combination of deterministic van der Waals assembly and directed intercalation chemistry.